KNOWLEDGE AND USAGE OF BODY MECHANICS AMONG CLASS IV WORKERS (International Journal of Physiotherapy, 2020)
Background: Body mechanics is the term used to describe the efficient, coordinated, and safe use of the body to move objects and carry out the activities of daily living.Methods: A descriptive co relational survey was conducted among 100 class IV workers of a tertiary hospital. The convenience sampling technique was used to select subjects. Baseline Proforma, a knowledge questionnaire on body mechanics, and a self-reported tool were used to collect the data.Results: Revealed that 64% of the subject had poor knowledge of body mechanics, 74% of Class IV worker's Usage of Body Mechanics during the work found to be poor, and a weak positive correlation was found between knowledge and usage (r =.091) of Body Mechanics among Class IV workers.Conclusion: The class IV workers are also considered an essential member of the health care team. The management's responsibility, including nurses, is to teach them how to use these techniques to prevent musculoskeletal injuries.